Mindfulness Stress Management for Female Cancer Survivors Facing the Uncertainty of Disease Progression: A Randomized Controlled Study - Jih-Teng Lee (International Journal of Environmental Research and Public Health, 2022)
This study aimed to determine the effect of a mindfulness stress management intervention on fear of recurrence and quality of life among female cancer survivors. A longitudinal, randomized design with two groups (60 participants) was used for pretest/posttest comparisons. Twelve weeks of mindfulness stress intervention effectively attenuated fear of recurrence symptoms (T1 p = 0.002, T2 p = 0.047), and quality of life (T1 p = 0.000, T2 p = 0.001) significantly increased. The results were significantly different between the intervention and control groups. Over time, group differences became more significant (T1 p = 0.002), demonstrating the effectiveness of the mindfulness stress management intervention. When female cancer survivors face uncertain disease progression, fear of recurrence affects their quality of life. When these women receive supportive intervention sooner, their improvement is more significant. Healthcare providers should encourage female cancer survivors to engage in mindfulness stress management actions to achieve a better benefit.